Change in sediment transport regime of the Keelung River in Taiwan induced by the operation of Yuanshantze flood diversion tunnel. - Tsung-Yu Lee; Tse-Yang Teng; Jun-Yi Lee; Yen-Wei Pan; Ming Chen; Chi-Cheng Chiu (PLoS ONE)
The impact of flood diversion channels on river sediment transport has been rarely reported. This study uses the Yuanshantze flood diversion tunnel (YFDT), which was commissioned in July 2005 in Taiwan, as an example. This study calculates the sediment transport in the Keelung River from 1997 to 2018 by using seasonal rating curves, in the form of aQb. Changes in rating curve coefficients are also analyzed to understand the impact of YFDT on sediment transport regime. The results show that after the construction of YFDT, the annual sediment transport dropped from 0.59 ± 0.47 [Mt y-1] to 0.17 ± 0.09 [Mt y-1], leading to dampened inter- and intra-annual variation. Before flood diversion, the Keelung River requires ~1% cumulative time to export 50% cumulated sediment loads, but it takes ~4.5% cumulative time after flood diversion. Exponent b decreased from 1.23±0.18 to 1.15±0.13, and log a decreased from 0.71±0.15 to 0.51±0.11, suggesting that the Keelung River is akin to a different river in terms of sediment transport regime. While the design of the diversion tunnel mainly considered its impact on flow, its impact on sediment transport is far greater than its impact on flow and should not be overlooked. Whether this new normality will affect the downstream river continuum requires continuous attention.